Between paternalism and illegality: a longitudinal analysis of the role and condition of manual scavengers in India. Issue 7 (22nd July 2022) - Saldanha, Sakshi; Kirchhelle, Claas; Webster, Emily; Vanderslott, Samantha; Vaz, Manjulika
Abstract : Manual scavengers, or 'Safai Karamcharis', as they are known in India, are sanitation workers who manually clean human waste for a living and face considerable occupational health risks. They are subject to deep-seated, caste-based stigma associated with their perceived 'caste impurity' and lack of cleanliness, which result both in consistently dangerous substandard working conditions and lack of social mobility, with women facing greater hardships. The COVID-19 pandemic has further exacerbated their plight. Despite the considerable efforts of social advocates, organised movements and government institutions, reforms and criminalisation have produced mixed results and campaigners remain divided on whether banning manual scavenging is an effective solution. This article reviews the history of attempts to address scavenging in India. Starting in the colonial period and ending with the current government's Swachh Bharat Mission, it highlights how attempts to deal with scavenging via quick-fix solutions like legal bans criminalising their employment, infrastructure upgrades or paternalistic interventions have either failed to resolve issues or exacerbated scavengers' situation by pushing long-standing problems out of view. It argues that meaningful progress depends on abandoning top-down modes of decision-making, addressing the underlying sociocultural and infrastructural factors that perpetuate the ill health and social conditions of manual scavengers, collecting data on the true extent of scavenging, and investing in and providing political agency to communities themselves.